Growth of three-dimensional diamond mosaics by microwave plasma-assisted chemical vapor deposition. Issue 2 (11th December 2017) - Shu, G.; Dai, B.; Ralchenko, V. G.; Bolshakov, A. P.; Khomich, A. A.; Ashkinazi, E. E.; Han, J.; Zhu, J.
Abstract : Growth of novel 3D diamond mosaic structures by MPCVD was realized, clearing the way for complex diamond shapes. Abstract : We realized the growth of a novel type of diamond mosaic crystal by chemical vapor deposition of a diamond layer on tightly placed oriented seed substrates, using a combination of seeds of different heights to form a three-dimensional structure. Here, a simple T-shaped mosaic is demonstrated as a proof of the principle. The 3D mosaic was epitaxially grown by microwave plasma CVD on (100)-oriented 3 × 3 × 1 mm 3 type Ib HPHT diamond substrates arranged horizontally and vertically. Very straight and sharp junctions between the vertical and horizontal parts were observed and characterized with SEM. Confocal Raman spectroscopy mapping of the CVD diamond layer revealed only a narrow (∼20 μm wide) zone of enhanced defect abundance and/or non-uniform stress, if any, around the junction. The Raman and photoluminescence mapping of the mosaic's cross-section gave further information on the spatial distribution of the epilayer with a thickness of up to 200 μm. The work demonstrates diamond growth on both sides of the vertically positioned seed plate, with a film thickness variation of less than 25%, thus doubling the diamond mass uptake achieved with the CVD process. The developed technique clears the way for the design and growth of various complex diamond shapes.